Antigen-non-specific T-cell factor in B-cell activation. Origin, biological properties and failure to show a relationship to H-2. - Waldmann, H; Poulton, P; Desaymard, C (1976)
A population of T cells sensitive to ALS treatment release a non-specific factor (NSF) capable of replacing T cells in the response of nude spleen cells to erythrocyte antigens. This factor cannot be removed by immunoadsorbents with specificities directed towards products of the H2 complex, nor by lentil lectin, unlike certain specific T-cell factors. Furthermore, it functions across histocompatibility differences between mouse strains. It has been directly demonstrated that this factor can influence both proliferation and differentiation of B cells in response to a restricted group of T-dependent antigens, of which donkey and sheep erythrocytes are such special cases.